INVESTMENT SERVICES AND ACTIVITIES AGREEMENT ON CAPITAL MARKET - Cristian GHEORGHE (Challenges of the Knowledge Society)
Investment services and activities on the account of the investors shall be supplied under a contract drafted in accordance with Capital Market Laws. Intermediaries (investment firms) hold the market access monopoly to trading systems of the regulated market or multilateral trading systems. Contracting them is the only way for investors to have access (indirectly) to trading through market orders. The legal framework shaped by the contract regarding investment services and activities is the premise, the mandatory and preliminary condition for the sale or purchase of financial instruments. The contract of investment services and activities is thus a sine qua non for trading on the capital market.